HPV infection and the immune microenvironment in cervical cancer - Li, Yibo; Deng, Jingui; Liu, Yayong; Yu, Shuangfeng (Frontiers in Immunology, 2025)
Cervical cancer remains a leading cause of cancer-related mortality in women, particularly in low-resource settings, despite advances in treatment modalities. The tumor immune microenvironment (TME) plays a pivotal role in cervical cancer pathogenesis, progression, and therapeutic response, driven largely by persistent HPV infection and subsequent immune evasion mechanisms. Clinical evidence supports the efficacy of pembrolizumab in PD-L1–positive recurrent/metastatic disease, while combinatorial strategies show promise in overcoming resistance. However, challenges persist, including biomarker identification and management of immune-related adverse events. This review elucidates the dynamic interplay between HPV-mediated immune suppression and the TME, highlighting the roles of tumor-associated macrophages (TAMs), regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs), and exhausted lymphocyte subsets in fostering an immunosuppressive milieu. Overall, this review integrates current advances in tumor immunology and immunotherapy, providing a comprehensive framework for developing precision-based strategies to improve outcomes in cervical cancer.